Building Bridges: Lessons Learned and Reflections from the Special Edition on Decolonial Perspectives from Latin America - Zambonini, Juan Pedro; Tosto, Virginia (Voices: A World Forum for Music Therapy, 2025)
This editorial introduces the special issue Perspectivas Decoloniales desde Latinoamérica, which gathers reflections from Latin American music therapists engaging critically with decolonial thought and practice. Drawing from the editorial process itself, we highlight six central themes that emerged through dialogue among authors, reviewers, and editors. First, we question the assumption that geographic location alone makes a practice decolonial, urging reflection on racism, inequality, and power relations within the Global South. Second, we explore identity as a relational and processual construct rather than an essential category. Third, we discuss how experiences of migration, marginalization, and privilege differently shape meanings of “decolonization” across contexts. Fourth, we affirm the scholarly legitimacy of reflective writing and practice-based essays alongside empirical research. Fifth, we invite attention to citation patterns and propose regional dialogue as a path toward situated knowledge. Finally, we share our decisions and challenges in translating texts across languages and cultural frames. We conclude by envisioning a plural, socially grounded, and liberatory music therapy that honors dignity, difference, and collective learning.